The Figure of the Modern Woman in Juan Ramón Molina and Charles Baudelaire during the Nineteenth and Twentieth Centuries - Luna Rodríguez, Allan (2026)
This research examines the transatlantic circulation of literary works between Hispanic America and Europe throughout the nineteenth and twentieth centuries. Its purpose is to investigate whether this exchange fostered a shared representation of Modernity while simultaneously shaping the construction of regional imaginaries. The analysis focuses on Les Fleurs du mal by the French poet Charles Baudelaire and Tierras, mares y cielos by the Honduran poet Juan Ramón Molina, with particular attention to the representation of the modern female figure in both works. The research adopts a mixed-methods and comparative framework, drawing upon Homi K. Bhabha’s concept of Dissémination and Gérald Froidevaux’s La représentation du présent. The findings reveal the presence of a common model of modernity underlying both authors’ poetics, alongside the distinctive cultural traits that differentiate them. This investigation contributes to the field of transatlantic literary studies and enhances the understanding of the impact of such exchanges on the evolution of literary history.